Effects of Viscosities and Solution Composition on Core-Sheath Electrospun Polycaprolactone(PCL) Nanoporous Microtubes - Yan Chen (MDPI AG, 2021)
Vascularization for tissue engineering applications has been challenging over the past decades. Numerous efforts have been made to fabricate artificial arteries and veins, while few focused on capillary vascularization. In this paper, core-sheath electrospinning was adopted to fabricate nanoporous microtubes that mimic the native capillaries. The results showed that both solution viscosity and polyethylene oxide (PEO) ratio in polycaprolactone (PCL) sheath solution had significant effects on microtube diameter. Adding PEO into PCL sheath solution is also beneficial to surface pore formation, although the effects of further increasing PEO showed mixed results in different viscosity groups. Our study showed that the high viscosity group with a PCL/PEO ratio of 3:1 resulted in the highest average microtube diameter (2.14 µm) and pore size (250 nm), which mimics the native human capillary size of 1–10 µm. Therefore, our microtubes show high potential in tissue vascularization of engineered scaffolds.